Advancing Clinical Trials in Nursing Homes: A Proposed Roadmap to Success. Issue 3 (23rd February 2022) - Gurwitz, Jerry H.; Quinn, Charlene C.; Abi‐Elias, Ivan H.; Adams, Alyce S.; Bartel, Rosie; Bonner, Alice; Boxer, Rebecca; Delude, Christopher; Gifford, David; Hanson, Bruce; Ito, Kouta; Jain, Paavani; et al.
Abstract: An effective clinical research effort in nursing homes to address prevention and treatment of COVID‐19 faced overwhelming challenges. Under the Health Care Systems Research Network‐Older Americans Independence Centers AGING Initiative, a multidisciplinary Stakeholder Advisory Panel was convened to develop recommendations to improve the capability of the clinical research enterprise in US nursing homes. The Panel considered the nursing home as a setting for clinical trials, reviewed the current state of clinical trials in nursing homes, and ultimately developed recommendations for the establishment of a nursing home clinical trials research network that would be centrally supported and administered. This report summarizes the Panel's recommendations, which were developed in alignment with the following core principles: build on available research infrastructure where appropriate; leverage existing productive partnerships of researchers with groups of nursing homes and nursing home corporations; encompass both efficacy and effectiveness clinical trials; be responsive to a broad range of stakeholders including nursing home residents and their care partners; be relevant to an expansive range of clinical and health care delivery research questions; be able to pivot as necessary to changing research priorities and circumstances; create a pathway for industry‐sponsored research as appropriate; invest in strategies to increase diversity in study populations and the research workforce; and foster the development of the next generation of nursing home researchers. Abstract : See related editorial by Zimmerman et al . and Special Articles by Levy et al . and Resnick et al . in this issue.